2015
DOI: 10.3109/13880209.2015.1089294
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory activity of several flavonoids isolated fromMurraya paniculataon murine macrophage cell line and gastric epithelial cell (GES-1)

Abstract: ORIGINAL ARTICLEThe anti-inflammatory activity of several flavonoids isolated from Murraya paniculata on murine macrophage cell line and gastric epithelial cell (GES-1) Context Murraya paniculata (L.) Jack (Rutaceae), Qianlixiang in Chinese, is distributed in China. As an important traditional Chinese medicine (TCM), it demonstrates many bioactivities, such as febrifuge, astringent, anti-dysenteric, and tonic. Objective: The objective of this study is to evaluate the anti-inflammatory effect of three flavonoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
(17 reference statements)
0
13
0
1
Order By: Relevance
“…2014 ; Wu et al. 2016 ). Few studies have been conducted with the essential oil of M. paniculata , and the majority of them have evaluated only the chemical composition, describing the presence of sesquiterpenes, such as β-caryophyllene, limonene, spathulenol and elemene (γ and δ), as major compounds (Chowdhury et al.…”
Section: Introductionmentioning
confidence: 99%
“…2014 ; Wu et al. 2016 ). Few studies have been conducted with the essential oil of M. paniculata , and the majority of them have evaluated only the chemical composition, describing the presence of sesquiterpenes, such as β-caryophyllene, limonene, spathulenol and elemene (γ and δ), as major compounds (Chowdhury et al.…”
Section: Introductionmentioning
confidence: 99%
“…In general, flavonoid aglycones have stronger anti-inflammatory activity than their corresponding glycosides [36], where the glycosylation of some substituent groups may bring an important effect on the activities. The double bonds, especially at C-2/C-3 of ring C, in the flavonoid structure play a critical role in the anti-inflammatory activity [37,38], but not in isoflavone according to the results of research. Compounds 7 , 9 , 11 , 12 , and 13 showed similar NO inhibitory activities but different downregulated mRNA expressions of inflammatory factors; this functional difference may be related to the number and position of hydroxyl groups.…”
Section: Discussionmentioning
confidence: 99%
“…Boonkusol (2017) reported that both crude extracts from Tamarindus indica seeds and Murraya paniculata leaves showed 100% larval mortality after in vitro 12 h incubation. According to Wu et al (2016) report, three flavonoids in glass-leaf extract exhibited anti-inflammatory activity in white blood cells and gastrointestinal mucosal cells, reducing the formation of nitric oxide and Interleukin-6. Phytochemicals in the two plants like flavonoids and oleanane type triterpenes may have had their independent or synergistic anthelmintic effects (Zafar et al, 2009).…”
Section: Discussionmentioning
confidence: 99%